Revealing An Examination of the Javanese People's Perspective on Uba Rampe of Traditional Marriage in Kendal Regency, Central Java - Wahyuni, Tri; Wiwin Erni Siti Nurlina (Southeast Asian Language and Literature Studies, 2025)
Marriage is a fundamental aspect of the human life cycle, serving not only as a sacred union between two individuals but also as a cultural tradition rich in symbolism and profound philosophical meanings passed down through generations. In Javanese culture, wedding ceremonies are more than mere rituals; they embody complex philosophies reflected through various elements called 'ubarampe' or ceremonial accessories used during traditional wedding processions. These ubarampe consist of various items that carry specific symbolic functions, collectively demonstrating the synergy of cultural and philosophical values within the community, especially in Boja Village, Kendal, Central Java. They serve as representations of the relationship between humans, nature, and divine principles, emphasizing harmony and balance—core concepts in Javanese cosmology—where elements such as water, fire, earth, and air symbolize fundamental aspects of life and the universe. Notably, earth and water dominate the ubarampe, symbolizing stability, fertility, and continuity, reflecting the community's view that success and harmony in marriage depend on maintaining equilibrium among these elements. This philosophy underscores the importance of humans aligning themselves with natural forces to achieve a harmonious and blessed life. Studying these symbols and their meanings reveals how traditional cultural practices strengthen local identity, preserve heritage, and foster a deeper understanding of life’s interconnectedness, emphasizing that cultural preservation is vital for sustaining community identity and ensuring the continuity of ancestral wisdom in contemporary society.